Quantitative MR imaging of intra-orbital structures: Tissue-specific measurements and age dependency compared to extra-orbital structures using multispectral quantitative MR imaging. (4th July 2017) - Watanabe, Memi; Buch, Karen; Fujita, Akifumi; Jara, Hernán; Qureshi, Muhammad Mustafa; Sakai, Osamu
ABSTRACT: The orbit can be affected by unique pathologic conditions and often requires MRI evaluation. The purpose of this study was to investigate the age-related changes in multiple intra-orbital structures using quantitative MRI (qMRI). Thirty-eight subjects (20 males, 18 females; ages 0.5–87 years) underwent MRI with a mixed turbo spin echo sequence. T1 and T2 measurements were obtained within ROI in 6 intra-orbital structures (medial and lateral rectus muscles, medial and lateral retrobulbar fat, lacrimal gland, and optic nerve), and compared with those of corresponding extra-orbital structures (masseter muscle, subcutaneous cheek fat, buccal fat, parotid gland, and frontal white matter). Statistical analyses were performed using Pearson's correlation coefficients. T1 and T2 values of the extra-ocular muscles increased with age, with higher T1 and T2 values compared to the masseter muscles. Retrobulbar fat showed significant age-associated increases in T1 values in the lateral side and in T2 values in both sides. T1 and T2 values in the lacrimal gland increased with age, while the parotid gland showed an age-associated increase in T2 values and decrease in T1 values. Optic nerves demonstrated age-related changes, similar to that of frontal white matter; rapid decreases with age in T1 and T2 times in early stages of life, and slight increases in T1 and T2 times later in life. Intra-orbital structures demonstrated specific qMRI measurements and aging patterns, which were different from extra-orbital structures. Location-specific age-related changes of intra-orbital structures should be considered in the qMRI assessment of the orbital pathology.